Surgical treatment of multiple cystic echinococcosis - Prousalidis, J (2004)
Background Multiple hydatid disease is a complex surgical problem, and its treatment can follow either conservative principles (drainage or obliteration of the cavity) or radical principles (cystoperi-cystectomy or liver or lung resection). Methods A total of 220 patients with multiple cystic echinococcosis (428 cysts) were managed between 1967 and 1998 with conservative operations (group A) or radical operation (group B). There were 90 men and 130 women, with a mean age of 52 years (range 18–77 years). There were two cysts in 124 patients, three cysts in 40 patients, four in 15 and more than four in 41 patients. These multiple cysts were located at one anatomical site (n=140) or at more than one site (n=80). Multiple (2–3) hepatic cysts occurred in 142 patients, multiple (2–3) lung cysts in 15 and multiple peritoneal cysts in 13 patients. Hepatic cysts co-existed with lung cysts in another 32 patients, with peritoneal cysts in 14 patients and once each with splenic, splenic plus lung cysts and renal cysts, one retroperitoneal cyst coincided with small peritoneal cysts. Results The operative procedure employed was dependent on the type and site of the parasite and the condition of the host. Three of 208 patients operated conservatively (group A) died postoperatively as opposed to receiving radical treatment. Morbidity rates were 8.8% and 12.5% in group A and B and mean hospital stay was 15.8 and 15.1 days, respectively. In group A there was an 8.6% recurrence rate, and recurrent disease was finally managed in each group the overall result could be considered satisfactory. Discussion We conclude that conservative surgery can provide good results in multiple cystic echinococcosis. Radical surgery, with its time-consuming major procedures, is ideal but only in properly selected cases.